In vivo anti-inflammatory, antipyretic, analgesic activity and in vitro anti-proliferative activity of aqueous methanolic extract of Euphorbia granulata Forssk - Mohsin Ahmad Ghauri; Liaqat Iqbal; Ali Raza; Uzma Hayat; Naveel Atif; Aqeel Javeed (SpringerOpen, 2021)
Abstract Background Naturally occurring substances of plant origin have long been used in folk medicine for curing various ailments including fever, pain, and inflammation etc. After careful evaluation on scientific bases, a large number of those substances provides cheaper alternative to currently used synthetic or semi-synthetic agents. Thus, with an aim of discovering alternative medicine for treatment of such ailments, current study was carried out. Euphorbia granulata Forssk. had long been used as a therapeutic agent against various morbid conditions, e.g., anthelmintic, snake bite, scorpion sting, purgative, and diuretic, and as blood purifying agent in folk medicine. The purpose of the current study was to determine the extended therapeutic use of Euphorbia granulata Forssk. based upon scientific evaluation, to explore the potential of its anti-proliferative, analgesic, antipyretic, and anti-inflammatory activities while using an aqueous methanol extract of the whole plant. Results In vivo study was performed on female rats of specie Rattus norvegicus weighing (100-150 g). Anti-inflammatory activity of the plant extract was calculated against using carrageenan induced paw edema. Analgesic potential both central and peripheral was assessed by using Eddy's hot plate method and acetic acid-induced writhing model, respectively. The antipyretic potential was appraised using brewer's yeast suspension, injected under the nape of the neck, and body temperature was measured using a digital thermometer. The plant extract strengths used for in vivo experiments were 50 mg, 100 mg, and 200 mg/kg (diluted in normal saline) and were administered through intra-peritoneal route. MTT assay was performed to estimate in vitro anti-proliferative potential. For this assay, a serial dilution of the plant extract was used with 100 μg/ml as the highest concentration. In vivo results demonstrated that plant extract at dose strength of 200 mg/kg, showed significant (p* < 0.05) anti-inflammatory, analgesic, and antipyretic activities. In case of MTT assay, however, no significant anti-proliferative activity (p > 0.05) was observed up to 100 μg/ml dose strength. Conclusion It can be concluded that aqueous methanol extract of Euphorbia granulata (whole plant) have shown significant anti-inflammatory, analgesic, and anti-pyretic activity in animal model. Therefore it can be a potential candidate, as a therapeutic alternative against treatment of algesia, pyrexia, and inflammation of various pathological origin. However, the plant extract did not demonstrate any significant anti-proliferation activity at doses used in this study.